Artificial Intelligence in Hadis Studies: A Systematic Review on The Opportunities, Applications and Ethical Challenges - Nur Afifi Alit; Shumsudin Yabi; Muhammad Fawwaz Muhammad Yusoff; Norhasnira Ibrahim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The rapid advancement of artificial intelligence has begun to reshape religious scholarship, including Hadith studies, by enabling large-scale authentication, textual analysis, and digital dissemination of Prophetic traditions. Despite these developments, the adoption of artificial intelligence in Hadith research raises persistent concerns regarding epistemic reliability, ethical integrity, and the preservation of scholarly authority, resulting in a fragmented and uneven body of literature. Methodology: To address this gap, this study conducts a systematic literature review to synthesise current research on the opportunities, applications, and ethical challenges of artificial intelligence in Hadith studies. Guided by the PRISMA protocol, relevant studies were identified through structured searches of Scopus, ProQuest, AskZad, and Google Scholar. After screening and eligibility assessment, 41 primary studies were included for qualitative synthesis. Results: The analysis yielded four main themes: AI for Hadith authentication and verification, AI-driven text processing, classification, and corpus development, AI applications for Hadith education, literacy, and information access, and ethical, epistemological, and normative challenges of AI in Hadith studies. Applications/Originality/Value: The findings show that artificial intelligence enhances efficiency, scalability, and accessibility across authentication, linguistic processing, and educational contexts, while simultaneously exposing risks related to fabrication, misinterpretation, bias, and authority displacement. This review concludes that artificial intelligence can meaningfully support Hadith scholarship only when integrated within robust ethical frameworks, sustained human oversight, and established principles of Islamic epistemology, ensuring that technological innovation reinforces rather than undermines the integrity of Prophetic knowledge.